Effect of salinity and soil temperature on the growth and physiology of drip-irrigated rice seedlings. Issue 4 (21st March 2017) - Bai, Ruxiao; Chen, Lin; Zhang, Xinjiang; Wei, Guohua; Wei, Changzhou
ABSTRACT: Drip irrigation offers potential for rice ( Oryza sativa L.) production in regions where water resources are limited. However, farmers in China's Xinjiang Province report that drip-irrigated rice seedlings sometimes suffer salt damage. The objective of this study was to learn more about the effects of soil salinity and soil temperature on the growth of drip-irrigated rice seedlings. The study consisted of a two-factor design with two soil salinity treatments (0 and 1.8 g kg −1 NaCl) and three soil temperature treatments (18°C, 28°C and 36°C). The results showed that shoot biomass, root biomass and root vigor were greatest when seedlings were grown with no salt stress (0 g kg −1 NaCl) at 28°C. Moderate salt stress (1.8 g kg −1 NaCl) combined with high temperature (36°C) significantly reduced root and shoot biomass by 39–53%. Moderate salt stress and high temperature also increased root proline concentration by 77%, root malonyldialdehyde concentration by 60% and seedling mortality by 60%. Shoot and root Na + concentrations, shoot and root Na + uptake and the Na + distribution ratio in shoots were all the greatest when moderate salt stress was combined with high temperature. In conclusion, high soil temperature aggravates salt damage to drip-irrigated rice seedlings. Therefore, soil salinity should be considered before adopting drip-irrigation for rice production.